(untitled) (Journal of Applied Learning and Teaching, 2021)
Books have a great influence on children’s self-esteem, behavior and thinking (Southard et al, 2014). Accordingly, when children picture books present stereotypical images of gender roles, children might be misled. Thus, the present study examines whether American males and females are equally portrayed in children’s literature or not. The purpose of this research paper is to examine the Caldecott Medal and Honor winners of children books in the 1940’s and the children picture books in 2000’s as they could have the greatest influence on how children would perceive stereotypical issues related to gender roles. Thus, the researchers carried out a close analysis of how the characters are exhibited in those picture books based on their gender roles, and whether this perspective has changed over time. The rationale for choosing these books is that they were bestsellers that time and also because of their impact on kids. The results show that female characters were presented less and with less important and more stereotyped roles than males.